EFFECT OF HYDROXAMATE SIDEROPHORES ON FE RELEASE AND PB(II) ADSORPTION BY GOETHITE - EFFICIENCY AND SPECIFICITY OF HYDROXAMATE SIDEROPHORES COMPARED TO ALIPHATIC ACIDS - Kraemer S.M.; Cheah S.F.; Zapf R.; Xu J.; Raymond K.N.; Sposito G. (My University, 1999)
Hydroxamate siderophores are biologically-synthesized, Fe(III)-specific ligands which are common in soil environments. In this paper, we report an investigation of their adsorption by the iron oxyhydroxide, goethite; their influence on goethite dissolution kinetics; and their ability to affect Pb(II) adsorption by the goethite surface. The siderophores used were desferrioxamine B (DFO-B), a fungal siderophore, and desferrioxamine D1, an acetyl derivative of DFO-B (DFO-D1). Siderophore adsorption isotherms yielded maximum surface concentrations of 1.5 (DFO-B) or 3.5 (DFO-D1) μmol/g at pH 6.6, whereas adsorption envelopes showed either cation-like (DFO-B) or ligand-like (DFO-D1) behavior. Above pH 8, the adsorbed concentrations of both siderophores were similar. The dissolution rate of goethite in the presence of 240 μM DFO-B or DFO-D1 was 0.02 or 0.17 μmol/g hr, respectively. Comparison of these results with related literature data on the reactions between goethite and acetohydroxamic acid, a monohydroxamate ligand, suggested that the three hydroxamate groups in DFO-D1 coordinate to Fe(III) surface sites relatively independently. The results also demonstrated a significant depleting effect of 240 μM DFO-B or DFO-D1 on Pb(II) adsorption by goethite at pH > 6.5, but there was no effect of adsorbed Pb(II) on the goethite dissolution rate.